2018
DOI: 10.3389/fvets.2018.00181
|View full text |Cite
|
Sign up to set email alerts
|

Lawsonia intracellularis: Revisiting the Disease Ecology and Control of This Fastidious Pathogen in Pigs

Abstract: Lawsonia intracellularis is an anaerobic obligate intracellular bacterium infecting the small intestine and infrequently also the large intestine of pigs and other animals including hamsters and horses. The infection is characterized by proliferation, hemorrhage, necrosis, or any combination commonly referred to as “ileitis,” affecting the health and production efficacy of farmed pigs. Despite decades of research on this pathogen, the pathogenesis and virulence factors of this organism are not clearly known. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 105 publications
2
78
0
5
Order By: Relevance
“…Like in our previous study in dogs [ 44 ], here NGS was found to be an effective non-targeted technique for the detection and characterisation of a diverse group of viruses and bacteria in pig colon and lung samples. The method was able to identify and quantify a relatively high abundance of the bacterium Lawsonia intracellularis , which was initially suspected by the veterinarian and subsequently identified by the histopathologist and could be consistent with the clinical disease, poor growth, and lesions observed [ 25 , 26 , 27 ]. Furthermore, it could also detect the presence of several species of Brachyspira and Campylobacter , which may have also been involved in the diarrhoea [ 28 , 29 , 30 , 31 ] and also demonstrated that Salmonella was not present in the samples similar to the microbiological testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like in our previous study in dogs [ 44 ], here NGS was found to be an effective non-targeted technique for the detection and characterisation of a diverse group of viruses and bacteria in pig colon and lung samples. The method was able to identify and quantify a relatively high abundance of the bacterium Lawsonia intracellularis , which was initially suspected by the veterinarian and subsequently identified by the histopathologist and could be consistent with the clinical disease, poor growth, and lesions observed [ 25 , 26 , 27 ]. Furthermore, it could also detect the presence of several species of Brachyspira and Campylobacter , which may have also been involved in the diarrhoea [ 28 , 29 , 30 , 31 ] and also demonstrated that Salmonella was not present in the samples similar to the microbiological testing.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that co-infection of PCV2 with porcine parvoviruses (PPVs), porcine bocaviruses (PBoVs), and torque teno sus viruses (TTSuVs) can be associated with porcine respiratory diseases complex (PRDC) [ 23 ] and PMWS [ 24 ]. Bacteria such as Lawsonia intracellularis [ 25 , 26 , 27 ], Brachyspira spp. [ 28 , 29 , 30 ], Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…The disease occurs in four different forms, namely: regional ileitis, intestinal adenomatosis, hemorrhagic enteropathy, necrotic enteritis. It is characterized by intestinal disorders and progressive weight loss in pigs (Lawson et al, 2000;McOrist et al, 2006;Karuppannan & Opriessnig, 2018;Leite et al, 2019). In general, Ileitis has a negative effect on pork's production, by reducing the average daily weight gain, feeding efficiency and deteriorating of the intestines function of the animals (Kukushkin et al, 2012;Jacobset al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of an in vitro model that represents the in vivo progression of PE has limited advancement in knowledge of the pathogenesis mechanisms utilized by L. intracellularis . Hence, identification of new alternatives for control and prevention of PE has been difficult, and pig producers and horse owners have been relying on available commercial vaccines (whole cell vaccines) and antimicrobials to prevent and control PE [710]. The costs associated with producing whole cell vaccines is reflected on the commercial price of the vaccines, hampering the access to some producers to the commercial vaccines, and, therefore preventing PE.…”
Section: Introductionmentioning
confidence: 99%